From the colonial borders of the Hispanic Empire in America to the international borders between independent Latin American states: the genesis of the impossibility of a consensual political map of South America - Lois, Carla (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
For centuries colonial boundaries in Latin America had been defined vaguely: they were administrative boundaries organising the administration of an extensive territory (for European canons), effectively occupied in a dispersed and irregular manner, with an archipelago of urban enclaves connected by the Camino Real (Royal Road).Since the wars of independence (1800 - 1860), many national territories were, de jure, defined from the principle of utis possidetis (the acceptance of old colonial administrative units for the new independent states) but, de facto, not effectively established as having territorial limits, giving rise to one of the greatest challenges for the nascent Latin American States. This was first due to the constant disagreement between the parties and second to the weaknesses in bureaucratic institutions lacking the materials, instruments and human resources to settle disputes.In addition, throughout the 19th century, hand-in-hand with the territorial formation of these modern states, there was a progressive reconceptualisation of the idea of the territorial limit, shifting from a strip or zone to a discrete, cartographic line. In practice, the 20th century saw old and new boundaries drawn and redrawn through complex negotiations, unstable alliances and military strife, some never settling and remaining today unresolved.Added to the technical and legal difficulties intrinsic to the demarcation of borders are national (and nationalist) historiographic traditions narrating stories of territorial formation and constructing arguments to sustain their territorial claims, making it literally impossible for the assembly of maps drawn up by the new Latin American nation states ever to result in a coherent political picture of Latin America.This article explores the variety of situations that were generated to solve the chimerical political map of South America and how the stories that the nation states created to narrate their territorial histories tended to build self-centred historiographies that ignored or blurred the global process of territorial formation in Latin America.
Keywords: Political map; Latin America; nation; borders; territorial demarcation